A novel strategy to improve the dyeing properties in laccase‐mediated coloration of wool fabric. (16th November 2016) - Zhang, Ting; Bai, Rubing; Wang, Qiang; Fan, Xuerong; Wang, Ping; Yuan, Jiugang; Yu, Yuanyuan
Abstract : Enzymatic coloration of fabrics has received worldwide attention in recent years. In order to improve the dyeing properties of enzymatically coloured fabrics, a novel strategy using 1‐ethyl‐3‐(3‐dimethylaminopropyl)carbodiimide hydrochloride (EDC), a biological coupling agent, to pretreat wool fabric was employed in this paper. Enzymatic coloration of wool fabrics with syringic acid was carried out in the presence of laccase from Trametes versicolor . The effect of different periods on laccase‐catalysed polymerisation of syringic acid was examined by UV‐vis spectroscopy. Enzymatic coloration results of dyed wool fabrics were evaluated by means of K / S value and colour difference ( ∆E* ). Process parameters, including the dosages of syringic acid and incubation time, that influenced the colour depth were studied. Meanwhile, the colour fastness and levelness of dyed wool fabrics were tested. The results showed that the UV‐vis absorbance of reaction solution increased as oxidation time elapsed, and a new peak appeared at 360 nm. After pretreatment, the K / S values and colour difference values of wool fabrics dyed with poly(syringic acid) improved appreciably compared with the control samples without any pretreatment. Moreover, pretreated wool fabrics showed better dyeing fastness and levelness than control samples.